Preliminary Study on ODS Alloy for Integrated Fast Reactor - LI Jing1, LI Junhong2, FENG Wei2, XIONG Liangyin1, LIU Shi1, LIU Yizhe2, LI Yiyi1, ZHOU Peide2 (Yuanzineng kexue jishu)
Due to the strong pinning to dislocations and grain boundaries as well as the available capturing of displaced atoms and helium bubbles, by oxide nanoparticles, oxide dispersion strengthened (ODS) alloys exhibit superior high-temperature mechanical properties, irradiation swelling resistance and corrosion resistance. ODS iron-based alloys have been considered as promising candidates for cladding tube and structural components of generation Ⅳ fission reactor and integrated fast reactor. In the present study, two variants of 12Cr-ODS FeCr alloys, i.e. carbon-free NFACN-1 and carbon-added NFACN-2 alloy, were fabricated by mechanical alloying and subsequent hot isostatic pressing. Then the rods with a diameter of 12.0 mm were obtained by using rotary swaging technology, and the alloy tubes with a diameter of 9.0 mm and a wall thickness of 0.65 mm were manufactured by Pilger cold rolling processes. The change in distribution, size and composition of nanoscale precipitates along the fabrication was characterized by TEM, HRTEM and APT techniques, and its effect on mechanical properties and thermophysical properties was evaluated. The results show that the nanoscale precipitates in the two alloys are predominantly Y2Ti2O7 particles with cubic pyrochlore phase, and the composition of oxide nanoparticles has not changed in the thermomechanical processing for rods and tubes fabrication. Nevertheless, some nanoscale precipitates have been coarsened, in which size growth for the tube fabrication is higher slightly than that for the rod fabrication. And the coarsening of nanoscale precipitates is also facilitated by the addition of a small amount of C. With the aid of thermophysical properties measurement from room temperature to 1 000 ℃, it is found that the instantaneous expansion coefficient and thermal conductivity of NFACN-1 and NFACN-2 alloys are less affected by the generation of nanoscale precipitates, compared to the non-ODS steel with similar components. However, an enhanced specific heat, especially in the temperature range of 400-800 ℃, is observed, which can be interpreted as the grain refinement caused by nanoscale precipitates pinning to the grain boundaries. This phenomenon indicates that the 12Cr-ODS FeCr alloys have a superior thermal inertia to the conventional casting alloy, which can absorb and release more heat without changing the temperature during the heating and cooling process. In addition, due to the generation of nanoscale precipitates with high density and chemical inertness, the rods exhibit outstanding creep resistance in the creep test at 650, 800 and 900 ℃, and the alloy tubes exhibit excellent high-temperature simultaneously longitudinal and circumferential strength and ductility.